4G Wireless network coverage prediction for operator “A” by using GIS in Jeddah City: a case study of Al Nuzhah district - Alhomrani, Noha Saeed; Ouerghi, Sarra Al Habib (Journal of natural sciences, life and applied sciences, 2020)
Communication systems depend on cell tower signals which affect the quality and efficiency of communications networks. In this paper, a prediction network coverage of 4G wireless network for operator “A” in Al Nuzhah city has been elaborated.The main objective is, firstly, to come up with prediction network maps showing the quality of communication networks in the study area and to identify areas with good and bad coverage, in order to maintain and improve coverage through relocating cell towers and antennas, increasing their number, or through installing new ones in bad coverage areas. Another objective is to compare this output with actual network coverage efficiency.In this study, GIS programs were adopted to handle, manage, process and analyze spatial and attribute data. GIS extensions were used to design communication networks such as the Mentum-Planet program through which prediction network coverage was calculated and represented. Cell towers and sectors data was first collected and then processed to generate the 4G coverage network prediction for operator "A" based on propagation model (Q9). Results were later compared to the network efficiency generated by the Drive Test.It was found that the signal strength was between -95 and -75 db. About 24.2% and 75.8% of the studied area had medium and excellent network coverage, respectively. The Drive Test showed areas of poor network coverage distributed throughout the study area.This research concluded that use of GIS in communications reduces cost and time of implementation. It is highly recommended to include building heights in the propagation model as it affects the spread of communication waves, to increase cell towers in poor coverage areas, and to modify the propagation model to ensure quality of service and efficient coverage.
Keywords: Prediction; cell towers coverage; 4G wireless network; network efficiency; GIS; Mentum-Planet